MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUIMEDIA PLASTISIN PADA ANAK USIA 5-6 TAHUN DI TK BHAKTI PERTIWI BATU HAMPAR KABUPATEN ROKAN HILIR - Roro Trijuli Astuti Kusuma Putri; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The background of this research is underdeveloped fine motor skills of children optimally among children may not be able: to mimic the ability of forms, exploring the various media and activities and cut according to the pattern.Therefore, researchers make improvements and optimize the fine motor skills of children according to age perkembangann level. The purpose of the implementation of this study was to determine the fine motor skills of children, to know how to perform activities using plasticine media so as to increase the fine motor skills of children, and to know how high plasticine media can improve fine motor skills of children in kindergarten B2 group Bakti Pertiwi Stone flagstones Rokan Hilir. This research is a classroom action research conducted in two cycles. In one cycle there are three meetings. Data collection tool used in this study is in the form of observation sheet. The number of samples in this study were 15 children, consisted of 6 boys and 9 girls.Based on the analysis of the assessment process there was an increase of 2 cycles. Improvement occurred, ie from before the action to the first cycle of 29.79%, the first cycle to the second cycle of 45.11%, and increased from the prior cycle to cycle II of 89.52%. From the results of these studies concluded that through the medium of clay can improve fine motor skills of children aged 5-6 years in kindergarten B2 group Bakti Pertiwi Stone Hampar Rokan Hilir.Keywords : Children Aged 5-6 Years, Media Playdough, Fine Motor.